A transformer‐based injection‐locked frequency divider. Issue 10 (5th June 2021) - Wan, Cao; Wu, Liang; Zhu, Haoshen; Xu, Taotao; Xue, Quan
Abstract: This letter reports a divide‐by‐four injection‐locked frequency divider with a transformer‐based fourth‐order tank. In the divider, the tank has two resonance peaks at ω0 and 3ω0  to enhance the injection efficiency, therefore, the locking range is enlarged. Besides, the divider contains a buffer for output third‐harmonic suppression. The proposed divider has been fabricated in 65 nm CMOS process with a die size of 0.535 mm 2, and the power consumption is 9.8 mW at 0.6 V supply voltage. The locking range is 12.1% from 27.8 to 31.4 GHz at 0 dBm power injection, the third‐harmonic rejection is over 18 dB in the whole band, and the best one is 22.9 dB.